A review of sustainable hydrogen energy by 2050: Supply chain, export markets, circular economy, social dimensions, and future prospects: Australia vs. worldwide - Seyed Mojib Zahraee; Nirajan Shiwakoti (Sustainable Futures, 2025)
Australia’s transition to a sustainable hydrogen economy by 2050 presents a transformative opportunity for decarbonization, economic growth, and global energy leadership. This review critically examines the state of hydrogen development in Australia, covering supply chains, export markets, circular economy integration, social dimensions, and policy implications. The analysis highlights the critical interplay between technological innovation, strategic government initiatives, and market demand as key enablers for large-scale hydrogen deployment by 2050. The paper identifies research gaps in harmonizing hydrogen development with circular economy principles, safety, social equity, and policy alignment. This work outlines clear policy implications, including the need for coordinated infrastructure investment, domestic market stimulation, international certification for exports, and integration of hydrogen into broader energy system planning. This work serves as a roadmap, synthesizing recent literature and addressing the challenges and opportunities, emphasizing cross-sector collaboration, regulatory reform, and targeted innovation investment. This review contributes a strategic framework to support decision-makers, industry partners, and researchers in advancing Australia’s hydrogen sector by 2050.